2020
DOI: 10.35940/ijitee.b6144.029420
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Street Trading Activities in Public Spaces (Ikorodu Motor Garage), Ikorodu, Lagos

Olabisi O. Ajakaiye,
Jubril Zakariyau,
Adedotun O. Akinola
et al.

Abstract: The present study examined socio-economic characteristics of commuters patronizing street traders, assessed factors responsible for patronizing street trader, investigated the perceived environmental hazard and assessed perceived spatial implications of street trading in Ikorodu motor park, Lagos State, Nigeria. The experimental survey research design was employed to first determine the average daily carrying capacity of the motor park (15,830 persons per day), while the sample size was 100, based on the Taro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[19] asserted that most of the hawkers and squatters that encroached on the roadside right of way or urban green space do that out of ignorance about the extant planning and development control laws and legislation and their presence in the space for economic survival attracts others that join them, and this constitutes free traffic flow hindrance and environmental sanitation issues. [6], [15], [17] revealed that the majority of those involved in the hawking, street trading and squatting activities by the roadside, open space or in the traffic are those with low levels of education or that haven't gone to school, so it is a survival venture for them because they lack the qualification that can make them be engaged into formal employment.…”
Section: Survival Strategies For the Unemployed Youthmentioning
confidence: 99%
See 3 more Smart Citations
“…[19] asserted that most of the hawkers and squatters that encroached on the roadside right of way or urban green space do that out of ignorance about the extant planning and development control laws and legislation and their presence in the space for economic survival attracts others that join them, and this constitutes free traffic flow hindrance and environmental sanitation issues. [6], [15], [17] revealed that the majority of those involved in the hawking, street trading and squatting activities by the roadside, open space or in the traffic are those with low levels of education or that haven't gone to school, so it is a survival venture for them because they lack the qualification that can make them be engaged into formal employment.…”
Section: Survival Strategies For the Unemployed Youthmentioning
confidence: 99%
“…The starting capital is low for hawking or street trade activities by vendors along the roads or in urban open spaces, this is according to [6], [16], [17], [20], so it is very easy to commence, and this is among the major factors that encourage or facilitate the low-income people of the society to engage in it.…”
Section: Low Starting Up Capital Venturementioning
confidence: 99%
See 2 more Smart Citations
“…Although this sector contributes significantly to employment at the global, continental and national stage, its operators encounter a lot of constraints. Other researchers in different countries have discovered that violence, poor hygiene, lack of business skills, municipal harassment, difficulty in accessing capital as some of the many constraints of informal operators (Ajakaiye et al, 2020;Fourie, 2018;Magalhães, 2015;Muthusamy & Ibrahim, 2016). Therefore, the current study set out to discover the constraints faced by informal street traders located in Durban (also known as the city of eThekwini), situated in the province of Kwa-Zulu Natal (one of South Africa's nine provinces).…”
Section: Introductionmentioning
confidence: 99%